An investigation into linguistic features of attitudinal expressions in ielts speaking tests - Phạm Thị Hoàng Nhật (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Evaluation is acknowledged as a product of the process specifying merit, worth, or significance (Scriven, 1991). Language assessment, the language of expressing personal feelings, is thus an indispensable part of practical communication to evaluate human behaviour, and by so doing, assess things or phenomena. This present study looks at the semantic features expressed via the language of Attitude in the sample answers of IELTS Speaking Test Part 2. Using the Appraisal framework by Martin and White (2005), the study identifies the realizations of language of Attitude identified through sample answers of IELTS Speaking Test Part 2. It examines the semantic features of different sub-categories of Attitude and then point out the lexical choice intended for successful meaning making in English. This paper is basically a descriptive piece of research. Using qualitative data collected on language of Attitude represented via a total of 107 sample answers, it has attempted to identify the semantic features in each sample before classifying them into three sub-categories of Attitude. The findings suggested that all sub-types of Affect and Judgement and Appreciation were found in the collected samples, among which, Affect has the highest rate of occurrences while the frequency of occurrences of Judgement records the lowest proportion. Moreover 83% of tokens of language denoting Attitude is positive and only 17% negative ones are found. The study has implications for language learning and teaching in a way that learners of English may need to have some knowledge of evaluative language in order to express their attitudes or feelings in an appropriate way for an appropriate circumstance or context. Besides, it teachers of English can find some useful insights with rich examples of language of evaluation in the authentic language resources.